2011
DOI: 10.1016/j.gep.2010.12.005
|View full text |Cite
|
Sign up to set email alerts
|

XLMR candidate mouse gene, Zcchc12 (Sizn1) is a novel marker of Cajal–Retzius cells

Abstract: Sizn1 (Zcchc12) is a transcriptional co-activator that positively modulates BMP (Bone Morphogenic Protein) signaling through its interaction with Smad family members and CBP. We have demonstrated a role for Sizn1 in basal forebrain cholinergic neuron specific gene expression. Furthermore, mutations in SIZN1 have been associated with X-linked mental retardation. Given the defined role of SIZN1 in mental retardation, knowing its complete forebrain expression pattern is essential to further elucidating its role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…could play an important role in the developmental regulation or maintenance of neuronal cells [68]. In addition, mutations of PNMA7A were found to be associated with human mental retardation [40,69]. Currently, it's not clear whether PNMA7A plays a role in neuronal survival or apoptosis; however, recent studies showed that PNMA7A functions as an oncogene and the expression is elevated in thyroid cancer cells [70,71], suggesting than PNMA7A could function to promote neuronal and cancer cell growths.…”
Section: Interaction With Transcription Factors and Growth Factorsmentioning
confidence: 99%
“…could play an important role in the developmental regulation or maintenance of neuronal cells [68]. In addition, mutations of PNMA7A were found to be associated with human mental retardation [40,69]. Currently, it's not clear whether PNMA7A plays a role in neuronal survival or apoptosis; however, recent studies showed that PNMA7A functions as an oncogene and the expression is elevated in thyroid cancer cells [70,71], suggesting than PNMA7A could function to promote neuronal and cancer cell growths.…”
Section: Interaction With Transcription Factors and Growth Factorsmentioning
confidence: 99%
“… Cho et al (2008a) , 2011 reported PNMA10 to be a candidate gene for X-linked mental retardation ( XLMR ) in humans. In mice, Pnma10/Zcchc12 is expressed in the embryonic ventral forebrain in a cholinergic–neuron-specific manner ( Cho et al, 2011 ), and is known to act as a transcriptional co-activator for bone morphogenic protein (BMP) signaling by binding to the SMAD family of proteins ( Cho et al, 2008b ). Therefore, it is likely that PNMA10 is related to the evolution of brain function in mammals.…”
Section: Pnma -Family Genes From the Gypsy12_dr-related Ltr mentioning
confidence: 99%
“…Cajal-Retzius cells have recently been suggested to be involved in cognition[ 6 ]. Cajal-Retzius cells may play a role in cognition, such as learning and memory, because alterations in the number of Cajal-Retzius cells have been suggested as a cause of neuronal dysfunction in Alzheimer's disease[ 51 ]. Cajal-Retzius cells and reelin have been implicated in neurological and psychiatric diseases, including Alzheimer's disease[ 25 52 ], temporal lobe epilepsy[ 18 53 ] and autism[ 54 55 ].…”
Section: Discussionmentioning
confidence: 99%